Implementasi Kebijakan Kawasan Pangan Nusantara Di Desa Talaga Kecamatan Dampelas Kabupaten Donggala - Safitri, Gita; Mufti, Moh. Irfan; Ferianto, Fiki (JPS: Journal of Publicness Studies, 2026)
This study analyzes the implementation of the Nusantara Food Area (KPN) policy in Talaga Village, Dampelas District, Donggala Regency, and identifies the challenges encountered. The research applies a qualitative case study approach, using Jan Merse’s policy implementation framework, which emphasizes information, policy content, community support, and resource allocation. The findings indicate that the implementation of KPN has not yet reached its target. By the end of 2025, only 185 hectares of land had been developed out of the planned 400 hectares. Program information has been disseminated, but unevenly across hamlets. The policy content aligns with local potential, yet the community mainly acts as implementers rather than planners. Public support is generally positive due to direct benefits such as infrastructure and seed distribution, although some residents remain concerned about environmental impacts. Resource allocation has been carried out, but distribution is uneven and land utilization is still constrained by technical and administrative issues. The study concludes that equitable information dissemination, stronger community involvement, continuous technical support, and improved coordination among stakeholders are essential for more effective and sustainable implementation of KPN in Talaga Village.